Polymyalgia rheumatica and giant cell arteritis: management of two diseases of the elderly. (August 2011) - Dejaco, Christian; Duftner, Christina; Dasgupta, Bhaskar; Matteson, Eric L; Schirmer, Michael
Both polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) present with a broad spectrum of clinical manifestations and almost exclusively occur in the population aged over 50 years. After rheumatoid arthritis, PMR is the second most common autoimmune rheumatic disorder. Visual loss is the most feared complication in temporal arteritis, and extracranial arteries and/or aorta are more often involved in GCA than previously estimated. No specific laboratory parameter exists for diagnosis of PMR. Imaging techniques such as ultrasonography, MRI or 18 F-fluorodeoxyglucose PET may be helpful in the diagnosis and evaluation of the extent of vascular involvement in these diseases. This article highlights upcoming new classification criteria for PMR, recent advances of diagnostic and therapeutic procedures as well as ongoing research on biomarkers and corticosteroid-sparing medications, which should improve management of PMR and GCA.